Explorations in the Indeterminacy of Computation: An Interview with M. Beatrice Fazi. (December 2021) - Beer, David
This interview with M. Beatrice Fazi explores in detail her work on computation. Focusing in particular upon her recent publications, it covers the themes of contingency and indeterminacy. The questions explore Fazi's perspectives on computational aesthetics, abstraction and experience. Through an interrogation of the conceptual insights that Fazi's recent work offers, the interview outlines an agenda for future work in the philosophy of computation and sets forward a series of conceptual policies for seeing the digital, software and data in a fresh light.